Baltazar de figueroa «the elder»: historiographical analysis, contributions and rectifications regarding his biography and provenance from seville (2012)
In the XVI century a family of artists appears in whatis now Colombia led by Baltazar de Figueroa, known as«The Elder». Only based on his painting style and withno additional documents some specialists attributed hima provenance from Seville. Gabriel Giraldo Jaramillo justifiedhis hypothesis with a group of documents that, afterthorough analysis and the discovery of some additionalones, led us to confirm that they refer to a homonymouspainter who never left the Spanish city.